The Role of Hormones and Toxoplasma gondii Infection to Change the Secondary Sex Ratio - Al-Ardi, Musafer H. (Iraqi Journal of Science, 2022)
The secondary sex ratio (SSR) is affected by many factors, including the concentration of hormones and infection with some pathogens such as Toxoplasma gondii. This study aimed to evaluate the effect of hormone variability concentrations and toxoplasmosis infection on the secondary sex ratio. 150 pregnant women were selected, 60 infected with late toxoplasmosis (LT), 60 infected with early toxoplasmosis (ET) and 30 seronegative to toxoplasmosis. After tracking the birth outcomes of these women, we calculated SSR in each group. During the second and third trimesters of pregnancy, estrogen, testosterone, progesterone, TSH, T4 and T3 concentrations were measured. The results of the three groups were compared. The results showed that female births outpaced in LT group, with SSR equal to (0.9:1.45), while the number of male births was higher in ET group and seronegative groups, with SSR was (1.5:1; 1.3:1), respectively. The difference in hormones concentration was significant at P ≥ 0.05. In LT group, progesterone and estrogen increased significantly in male pregnant women than in female pregnant women. Testosterone increased significantly in male pregnant women in all study groups. TSH level was the highest among female pregnant women in the LT and seronegative groups. The superiority of male pregnant women in the concentration of T3 hormone in all groups was significant. Male pregnant women were significantly superior with T4 concentration in LT and seronegative groups.In conclusion, T. gondii has an indirect role in SSR. Important pregnancy hormones levels differ between male pregnant women and female pregnant women.In conclusion, T. gondii has an indirect role in SSR. Important pregnancy hormones levels differ between male pregnant women o and female pregnant women.